Colorant-coated silicon-modified acrylate-styrene-acrylonitrile graft copolymer, composition containing same, and preparation method thereof

By using a nano-scale colorant emulsion and a polysiloxane-based latex for polymerization and grafting reaction in high-gloss black ASA parts, silicon modified acrylate-styrene-acrylonitrile graft copolymer coated with colorants was prepared, which solved the problem that it was difficult to meet the blackness requirements of the parts in the prior art, and achieved higher blackness and weather resistance.

CN119823333APending Publication Date: 2025-04-15SHINE POLYMER (ZHUHAI) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510033649.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art has difficulty meeting the customer's requirements for the blackness of the product after adding saturated colorants to the high-gloss black ASA products.

Method used

By dispersing the colorant in an emulsifier solution to form a nano-scale colorant emulsion, and polymerizing the polysiloxane-based latex with acrylate in the presence of the colorant to obtain a rubber phase coated with the colorant, and then grafting it with styrene and acrylonitrile to prepare a silicon modified acrylate-styrene-acrylonitrile graft copolymer coated with the colorant.

Benefits of technology

It is achieved that a silicon modified acrylate-styrene-acrylonitrile graft copolymer with higher blackness is obtained under the same amount of coloring agent, which improves the coloring and weathering resistance of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005234901130000121
    Figure BDA0005234901130000121
  • Figure BDA0005234901130000131
    Figure BDA0005234901130000131
  • Figure BDA0005234901130000132
    Figure BDA0005234901130000132
Patent Text Reader

Abstract

The invention relates to a preparation method of a silicon modified acrylate-styrene-acrylonitrile graft copolymer coated with a coloring agent. The preparation method comprises the following steps: dispersing the coloring agent in a solution of an emulsifier to form a nanoscale coloring agent emulsion; the preparation method comprises the following steps: polymerizing polysiloxane latex and acrylate in the presence of a nanoscale colorant emulsion to obtain a rubber phase coated with a colorant; and grafting the obtained rubber phase with styrene and acrylonitrile to obtain the emulsion of the silicon modified acrylate-styrene-acrylonitrile grafted copolymer coated with the coloring agent. According to the preparation method disclosed by the invention, the silicon modified acrylate-styrene-acrylonitrile grafted copolymer coated with the coloring agent can be obtained, and a product with higher blackness can be obtained by adding the silicon modified acrylate-styrene-acrylonitrile grafted copolymer into resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and particularly relates to a method for preparing a colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer, a colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer obtained by the preparation method, and a composition containing the colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer. Background Art

[0002] The terpolymer of acrylonitrile (A), butadiene (B), and styrene (S) (ABS) is a widely used thermoplastic general engineering plastic with excellent impact resistance, low temperature resistance, gloss, as well as excellent coloring performance, electrical properties and mechanical properties. However, the presence of C=C unsaturated double bonds in polybutadiene rubber in ABS makes ABS have poor weather resistance, limiting its use in outdoor environments. Acrylate-styrene-acrylonitrile graft copolymer (ASA) is a terpolymer with a core-shell structure synthesized by emulsion polymerization with acrylate (Acrylate), styrene (St), and acrylonitrile (AN) as the main reaction raw materials. ASA greatly improves the weather resistance of ASA by using acrylate (such as butyl acrylate) to replace butadiene in ABS, and can be widely used in outdoor scenes, such as ASA resin tiles, automotive accessories, outdoor appliances, power tools, etc. However, it is also because of the use of acrylate to replace butadiene that the coloring performance of ASA high-rubber powder is slightly worse than that of ABS high-rubber powder.

[0003] With the development of new energy vehicles in recent years and the enhancement of environmental awareness, spray-free, high-gloss black ASA parts are popular among consumers, and are therefore widely used in automobile grille bodies, rearview mirror housings, column decorative panels, tailgate decorative panels, etc.

[0004] In the above-mentioned application fields of ASA parts that require the blackness of high gloss black, it is usually necessary to add saturated colorants (carbon black, black masterbatch, black organic dyes, etc.) to the appropriate ASA high-gloss powder in the modification process to improve the appearance blackness of the parts. However, due to the poor coloring performance of ASA and / or the dispersibility of the colorant in the ASA high-gloss powder, even if the appropriate high-gloss powder and colorant are selected and the amount of colorant added reaches saturation, it is still difficult to meet the customer's requirements for the blackness of the parts. Chinese patent applications CN 109401103 A, CN113416372 A, CN112552614A, CN111690222A, etc. report the preparation and application of spray-free high gloss black styrene-acrylonitrile copolymer / ASA (AS / ASA) resin composition or polymethyl methacrylate / ASA (PMMA / ASA) alloy material. Summary of the invention

[0005] Problems to be solved by the invention

[0006] However, in the technologies disclosed in the above documents, colorants need to be added externally and even after the amount of colorant added reaches saturation, the blackness requirement of the product cannot be met.

[0007] In view of the above facts, the subject of the present invention is to provide a method for preparing a silicon-modified acrylate-styrene-acrylonitrile graft copolymer of a coated colorant that can have a higher blackness under the premise of adding the same amount of colorant, and to provide a silicon-modified acrylate-styrene-acrylonitrile graft copolymer of a coated colorant obtained by the method and a composition containing the silicon-modified acrylate-styrene-acrylonitrile graft copolymer of the coated colorant.

[0008] Solutions to Solve Problems

[0009] After a series of studies, the inventors found that in the presence of a nanoscale colorant emulsion formed by a colorant and an emulsifier solution, a polysiloxane latex and an acrylate are polymerized to obtain a rubber phase in which the colorant is encapsulated, and then styrene and acrylonitrile are grafted onto the obtained rubber phase to obtain a silicon-modified acrylate-styrene-acrylonitrile graft copolymer encapsulating the colorant, thereby preparing a silicon-modified acrylate-styrene-acrylonitrile graft copolymer encapsulating the colorant with higher visual blackness and improved weather resistance.

[0010] The first aspect of the present invention provides a method for preparing a colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer, comprising the following steps: dispersing the colorant in an emulsifier solution to form a nano-scale colorant emulsion; polymerizing a polysiloxane latex with an acrylate in the presence of the nano-scale colorant emulsion to obtain a rubber phase encapsulated with the colorant; and grafting the obtained rubber phase with styrene and acrylonitrile to obtain an emulsion of the colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer.

[0011] Furthermore, in the first aspect, the colorant is selected from carbon black or black organic dyes.

[0012] According to the blackness requirements of styrene-acrylonitrile copolymer / acrylate-styrene-acrylonitrile graft copolymer (AS / ASA) resin composition, polymethyl methacrylate / acrylate-styrene-acrylonitrile graft copolymer (PMMA / ASA) alloy material, polycarbonate / acrylate-styrene-acrylonitrile graft copolymer (PC / ASA) resin composition, polybutylene terephthalate / acrylate-styrene-acrylonitrile graft copolymer (PBT / ASA) resin composition, etc. for high gloss black, when the total addition amount of the solid component of the above-mentioned polysiloxane latex, the above-mentioned acrylate, the above-mentioned styrene, and the above-mentioned acrylonitrile is calculated as 100 parts by weight, the addition amount of the colorant is 0.3-3 parts by weight. Preferably, when the colorant is carbon black, the addition amount is 0.5-2.3 parts by weight; when the colorant is a black organic dye, the addition amount is 0.5-1.2 parts by weight.

[0013] Furthermore, in the first aspect, the emulsifier used to disperse the colorant is selected from one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, dodecylbenzene sulfonic acid and its sodium salt, potassium oleate, sodium stearate, disproportionated potassium rosin soap, dioctyl sodium sulfosuccinate, sodium salt of dihexyl sulfosuccinate and polyethylene glycol trimethyl nonyl ether (TMN-10), preferably a compound of sodium dodecyl sulfate and potassium oleate.

[0014] Furthermore, in the first aspect, the compounding ratio of the sodium lauryl sulfate and potassium oleate is 1:2-2:1.

[0015] Furthermore, in the first aspect, when the total amount of the solid content of the above-mentioned polysiloxane latex, the above-mentioned acrylate, the above-mentioned styrene, and the above-mentioned acrylonitrile is calculated as 100wt%, the addition amount of the above-mentioned polysiloxane latex in terms of solid content is 2-10wt%, preferably 3-6wt%; the addition amount of the above-mentioned acrylate is 48-58wt%, preferably 50-55wt%; the addition amounts of the above-mentioned styrene and the above-mentioned acrylonitrile are 25-40wt% and 10-25wt%, respectively; wherein the above-mentioned styrene accounts for 67-80wt%, preferably 70-78wt% of the total amount of the above-mentioned styrene and the above-mentioned acrylonitrile.

[0016] Furthermore, in the first aspect, the polysiloxane latex is a latex of a linear polysiloxane having a vinyl group, and the content of the vinyl group in the polysiloxane latex is 0.01 to 3 wt % based on the solid content in the polysiloxane latex.

[0017] Furthermore, in the first aspect, the polysiloxane latex is obtained by polymerizing a dimethylsiloxane monomer, a vinylsiloxane monomer, and, if necessary, a capping agent, and the polysiloxane latex has a number average molecular weight Mn of 200,000 to 600,000.

[0018] Furthermore, in the first aspect, the dimethylsiloxane monomer is selected from one or more of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane;

[0019] The vinyl siloxane monomer is selected from one or more of γ-(meth)acryloxypropyldimethoxymethylsilane, γ-(meth)acryloxypropyldiethoxymethylsilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, and tetramethyltetravinylcyclotetrasiloxane;

[0020] The capping agent is selected from one or more of hexamethyldisiloxane, tetramethyldivinyldisiloxane, methoxytrimethylsilane, ethoxytrimethylsiloxane, dimethylvinylmethoxysilane, and dimethylvinylethoxysilane.

[0021] Furthermore, in the first aspect, the particle size of the latex of the silicon-modified acrylate-styrene-acrylonitrile graft copolymer encapsulating the colorant is 80-200 nm, preferably 100-150 nm.

[0022] Furthermore, in the first aspect, the rubber phase coated with the colorant is obtained by polymerizing the polysiloxane latex and the acrylate using a crosslinking agent. The crosslinking agent is selected from one or more of divinylbenzene, dicyclopentadiene acrylate, allyl methacrylate, diallyl phthalate, mono[2(1-oxy-2-propenyl)oxyethyl] maleate, and trimethylolpropane triacrylate, preferably dicyclopentadiene acrylate.

[0023] Furthermore, in the first aspect, the emulsion of the silicon-modified acrylate-styrene-acrylonitrile graft copolymer coated with the colorant is obtained by grafting the rubber phase coated with the colorant with the styrene and the acrylonitrile using an initiator. The initiator is selected from one or more of azobisisobutyronitrile, potassium persulfate, ammonium persulfate, glucose, vitamin C, cumene hydroperoxide, and tert-butyl hydroperoxide, preferably glucose and / or cumene hydroperoxide.

[0024] Furthermore, in the first aspect, the method further comprises the step of preparing a high-rubber powder from the emulsion of the colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer.

[0025] In addition, the second aspect of the present invention provides a colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer obtained by the preparation method described in the first aspect.

[0026] Furthermore, in the second aspect, the number average molecular weight (Mn) of the above-mentioned silicon-modified acrylate-styrene-acrylonitrile graft copolymer encapsulating the colorant is 40,000-70,000 (preferably 57,000), the weight average molecular weight (Mw) is 110,000-140,000 (preferably 128,000), and the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) is 2.1-3.4 (preferably 2.2-2.8, more preferably 2.25).

[0027] The third aspect of the present invention provides a composition comprising the colorant-encapsulating silicon-modified acrylate-styrene-acrylonitrile graft copolymer according to the second aspect and a resin.

[0028] Furthermore, in the third aspect, the resin is selected from one or more of styrene-acrylonitrile copolymer (AS), polymethyl methacrylate (PMMA), polycarbonate (PC), polybutylene terephthalate (PBT), polystyrene (PS), (meth)acrylate-styrene copolymer (MS), acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-ethylene-propylene rubber-styrene copolymer (AES), and polyethylene terephthalate (PET). Preferably, one or more of AS, PMMA, and PC are selected.

[0029] Furthermore, in the third aspect, the composition is a resin composition or an alloy material.

[0030] Furthermore, in the third aspect, the content of the silicon-modified acrylate-styrene-acrylonitrile graft copolymer encapsulating the colorant is 28-40 wt %, preferably 30-36 wt %.

[0031] Furthermore, in the third aspect, the resin composition is an AS / ASA resin composition, including a styrene-acrylonitrile copolymer and the silicon-modified acrylate-styrene-acrylonitrile graft copolymer of the above-mentioned coated colorant; and the alloy material is a PMMA / ASA alloy material, including polymethyl methacrylate and the silicon-modified acrylate-styrene-acrylonitrile graft copolymer of the above-mentioned coated colorant.

[0032] Effects of the Invention

[0033] According to the present invention, a method for preparing a colorant-coated silicon-modified acrylate-styrene-acrylonitrile graft copolymer can be provided, wherein the preparation method can copolymerize polysiloxane, acrylate, styrene and acrylonitrile to form a colorant-coated silicon-modified acrylate-styrene-acrylonitrile graft copolymer having higher coloring performance and weather resistance. When the colorant-coated silicon-modified acrylate-styrene-acrylonitrile graft copolymer obtained by the above preparation method is mixed with resin AS or PMMA, a composition with better coloring degree can be obtained. The composition of the present invention can be widely used in high-gloss black ASA products such as automobile grille bodies, rearview mirror housings, pillar decorative panels, tailgate decorative panels, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Shown is a transmission electron microscope photograph of the carbon black emulsion (C1) obtained in Example 1.

[0035] Figure 2 Shown is a transmission electron microscope photograph of the carbon black-coated silicon-modified ASA emulsion (A2) obtained in Example 1. DETAILED DESCRIPTION

[0036] First, the method for preparing the colorant-coated silicon-modified acrylate-styrene-acrylonitrile graft copolymer of the present invention is described.

[0037] The preparation method of the colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer of the present invention comprises the following steps: dispersing the colorant in an emulsifier solution to form a nano-scale colorant emulsion; in the presence of the nano-scale colorant emulsion, polymerizing the polysiloxane latex and acrylate through a crosslinking agent to obtain a rubber phase encapsulated with the colorant; and grafting the obtained rubber phase with styrene and acrylonitrile through an initiator to obtain an emulsion of the colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer. The emulsion of the colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer can be further made into high-rubber powder by conventional methods in the art.

[0038] According to the preparation method of the present invention, a silicon-modified acrylate-styrene-acrylonitrile graft copolymer coated with a colorant can be obtained. The graft copolymer is coated with a colorant. When added to a resin, the dispersibility of the colorant in the composition (especially the AS / ASA resin composition or the PMMA / ASA alloy material) can be improved, thereby improving the coloring performance of the colorant powder. Compared with the AS / ASA resin composition and the PMMA / ASA alloy material formula in which the same weight of colorant is added, the present invention can obtain a composition with a higher visual blackness. At the same time, the colorant added (dispersed) in the traditional way is easy to precipitate on the surface, resulting in poor weather resistance, while the graft copolymer provided by the present invention is coated with a colorant, so that the speed at which the colorant migrates to the surface is slower, so as to improve the original weather resistance of ASA.

[0039] The polysiloxane latex used in the preparation method of the present invention is not limited. Specifically, the polysiloxane latex described in Chinese patent application CN106519144A can be used, and more preferably a latex of a straight-chain polysiloxane having a vinyl group (active functional group). Preferably, the vinyl content in the polysiloxane latex is 0.01 to 3% by mass relative to 100% by mass of the solid content in the polysiloxane latex; its lower limit is preferably 0.02% by mass, more preferably 0.1% by mass, and further preferably 0.8% by mass; its upper limit is preferably 2.5% by mass, more preferably 2% by mass, and further preferably 1% by mass.

[0040] The polysiloxane latex can be obtained by polymerizing a dimethylsiloxane monomer, a vinylsiloxane monomer, and, if necessary, a capping agent. It is preferred that no crosslinking agent be used in the production of the polysiloxane latex of the present invention.

[0041] Specific examples of the dimethylsiloxane monomers include hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, etc. These monomers may be used alone or in combination of two or more. Among them, octamethylcyclotetrasiloxane is preferably used from the viewpoint of easy control of particle size distribution.

[0042] Specific examples of the above-mentioned vinylsiloxane monomers include γ-(meth)acryloxypropyldimethoxymethylsilane, γ-(meth)acryloxypropyldiethoxymethylsilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, tetramethyltetravinylcyclotetrasiloxane, etc. These may be used alone or in combination of two or more.

[0043] Specific examples of the head sealing agent include hexamethyldisiloxane, tetramethyldivinyldisiloxane, methoxytrimethylsilane, ethoxytrimethylsiloxane, dimethylvinylmethoxysilane, and dimethylvinylethoxysilane. These may be used alone or in combination of two or more.

[0044] As for the method for producing the polysiloxane latex, the following method can be mentioned.

[0045] First, a mixed monomer containing dimethylsiloxane monomers, vinylsiloxane monomers and a capping agent as required is mixed with an emulsifier, an acid catalyst, water, etc., and pre-emulsified to obtain a monomer emulsion. Then, the monomer emulsion is polymerized at a certain temperature. Finally, the acid is neutralized with an alkaline substance to obtain a polysiloxane latex.

[0046] The number average molecular weight (Mn) of the above-mentioned polysiloxane latex is preferably 200,000-600,000; its lower limit is more preferably 220,000, more preferably 240,000, and further preferably 260,000; its upper limit is more preferably 500,000, more preferably 400,000, and further preferably 300,000.

[0047] Specific examples of the colorant include carbon black and black organic dyes, and these may be used alone or in combination of two or more.

[0048] As specific examples of the emulsifier for dispersing the colorant, for example, sodium lauryl sulfate, sodium lauryl sulfonate, dodecylbenzene sulfonic acid and its sodium salt, potassium oleate, sodium stearate, disproportionated rosin acid potassium soap, dioctyl sodium sulfosuccinate, sodium salt of dihexyl sulfosuccinate, TMN-10, etc. can be listed. These can be used alone or in combination of two or more, preferably sodium lauryl sulfate and potassium oleate. The compounding ratio of sodium lauryl sulfate and potassium oleate is 1:2-2:1.

[0049] Specific examples of the acrylic acid ester include butyl acrylate, methyl acrylate, ethyl acrylate, isooctyl acrylate, and the like. These may be used alone or in combination of two or more. Butyl acrylate is preferred.

[0050] Specific examples of the crosslinking agent used when the polysiloxane latex and acrylate are polymerized include divinylbenzene, dicyclopentadiene acrylate, allyl methacrylate, diallyl phthalate, maleic acid mono[2(1-oxy-2-propenyl)oxyethyl] ester, trimethylolpropane triacrylate, etc. These can be used alone or in combination of two or more, preferably dicyclopentadiene acrylate. When the total amount of the polysiloxane latex as solid content, the colorant emulsion as solid content of the colorant, and the acrylate is 100 parts by weight, the amount of the crosslinking agent added is 0.5-2 parts by weight, preferably 0.8-1 part by weight.

[0051] In the present invention, the rubber phase coated with the colorant is grafted with styrene and acrylonitrile by an initiator to obtain a silicon-modified ASA emulsion coated with the colorant. The particle size of the silicon-modified ASA emulsion coated with the colorant is 80-200nm, preferably 100-150nm.

[0052] Specific examples of the initiator used above include azobisisobutyronitrile, potassium persulfate, ammonium persulfate, glucose, vitamin C, cumene hydroperoxide, tert-butyl hydroperoxide, etc. These can be used alone or in combination of two or more, preferably glucose and / or cumene hydroperoxide.

[0053] In the preparation method of the silicon-modified ASA coated with a colorant of the present invention, when the total amount of the solid content, acrylate, styrene and acrylonitrile of the polysiloxane latex is calculated as 100wt%, the added amount of the polysiloxane latex in terms of solid content is 2-10wt%, preferably 3-6wt%; the added amount of acrylate is 48-58wt%, preferably 50-55wt%; the added amount of styrene is 25-40wt%; the added amount of acrylonitrile is 10-25wt%; wherein styrene accounts for 67-80wt%, preferably 70-78wt% of the total amount of styrene and acrylonitrile.

[0054] In addition, regarding the silicon-modified ASA coated with a colorant obtained by the preparation method of the present invention, its number average molecular weight (Mn) is 40,000-70,000 (preferably 57,000), the weight average molecular weight (Mw) is 110,000-140,000 (preferably 128,000), and the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) is 2.1-3.4 (preferably 2.2-2.8, more preferably 2.25).

[0055] The composition of the present invention contains silicon-modified ASA coated with a colorant and a resin. The silicon-modified ASA coated with a colorant is usually added to the resin in the form of a powder. The powder of the silicon-modified ASA coated with a colorant is finally obtained by subjecting the silicon-modified ASA emulsion coated with a colorant obtained by the above preparation method to a series of post-treatment processes such as coagulation, drying, and crushing, so as to obtain the powder of the silicon-modified ASA coated with a colorant (such as high-rubber powder).

[0056] Specific examples of the above resins include styrene-acrylonitrile copolymer (AS), polymethyl methacrylate (PMMA), polycarbonate (PC), polybutylene terephthalate (PBT), polystyrene (PS), (meth)acrylate-styrene copolymer (MS), acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-ethylene-propylene rubber-styrene copolymer (AES), and polyethylene terephthalate (PET). These resins may be used alone or in combination of two or more, preferably one or more of styrene-acrylonitrile copolymer (AS), polymethyl methacrylate (PMMA), and polycarbonate (PC).

[0057] The above-mentioned composition may be a resin composition or an alloy material, and examples thereof include an AS / ASA resin composition formed by combining a colorant-coated silicon-modified ASA with AS; and a PMMA / ASA alloy material formed by combining a colorant-coated silicon-modified ASA with PMMA.

[0058] The content of the silicon-modified ASA of the coated colorant in the composition is preferably 28-40wt%, more preferably 30-36wt%, and further preferably 34-36wt% relative to 100wt% of the composition. When the content of the silicon-modified ASA of the coated colorant is 40wt% or more, the obtained composition may have problems such as low processing fluidity and excessive saturation due to excessive addition of the silicon-modified ASA of the coated colorant; when the content of the silicon-modified ASA of the coated colorant is less than 28wt%, the impact properties may decrease due to the low addition of the silicon-modified ASA of the coated colorant, and the blackness requirement of high gloss black may not be met due to the low addition of the silicon-modified ASA of the coated colorant.

[0059] The composition preferably further contains one or more of the commonly used antioxidants, lubricants, and weathering agents. Examples of the antioxidant include antioxidant 1076 and antioxidant 168. Examples of the lubricant include vinyl bis stearamide (EBS) and pentaerythritol stearate (PETS). Examples of the weathering agent include ultraviolet absorber 234 (UV 234), ultraviolet absorber UV-P, and ultraviolet absorber UV-770DF.

[0060] The measurement of various physical properties in the present invention was carried out by the following methods.

[0061] (1) Impact strength

[0062] Impact strength is tested according to ASTM D256 and is expressed in kJ / m 2 )express.

[0063] (2) Melt index

[0064] The melt index is tested according to ASTM 1238 standard, and the test conditions are: 220°C, 10kg.

[0065] (3) Coloring

[0066] The coloring adopts the GB / T 7921-2008 method to make a standard color plate, and the test is carried out using a colorimeter (CM-5 colorimeter from Konica Minolta) under D65 light source according to the CIE evaluation standard.

[0067] (4) Glossiness

[0068] The glossiness was tested using the ASTM D523-2014 standard method, with a standard color plate made and a gloss meter (NHG268, Shenzhen Sanenshi Technology Co., Ltd.) at a test angle of 60°.

[0069] Example

[0070] The present invention will be described in further detail below in conjunction with Examples, but embodiments of the present invention are not limited thereto. Unless otherwise specified, the materials and methods involved in the Examples are materials and methods commonly used in the art. In addition, "parts" and "%" in this specification, unless otherwise specified, represent "parts by weight" and "% by weight" respectively.

[0071] Example 1

[0072] (1) Preparation of polysiloxane latex

[0073] (1-1) A mixture of 61 parts of deionized water and 0.6 parts of dodecylbenzenesulfonic acid was added to a four-necked flask equipped with an electric stirrer, a constant pressure dropping funnel, a thermometer and a condenser, the stirrer was turned on, and the temperature was raised to 70° C. and kept constant. Then, 1.6 parts of hexamethylcyclotrisiloxane, 28 parts of octamethylcyclotetrasiloxane and 3 parts of γ-(meth)acryloxypropyldimethoxymethylsilane were mixed evenly as a dropwise component and added dropwise using a constant pressure dropping funnel. The mixture was added dropwise over 2 hours and kept warm for 2 hours after the addition was completed.

[0074] (1-2) 124 parts of deionized water, 1 part of sodium dodecylbenzene sulfonate, 3.4 parts of hexamethylcyclotrisiloxane, 57 parts of octamethylcyclotetrasiloxane, 5 parts of γ-(meth)acryloxypropyldiethoxymethylsilane and 2 parts of hexamethyldisiloxane were mixed and homogenized in a high shear homogenizer. Then, the mixture was added dropwise to the above system using a constant pressure dropping funnel. After the mixture was added over 4 hours, the temperature was raised to 80°C and kept warm for 10 hours.

[0075] (1-3) After the polymerization is completed, the emulsion is cooled to room temperature and neutralized with ammonia water to a pH value of 7-8 to obtain polysiloxane latex (G1).

[0076] (2) Preparation of nano-scale colorant emulsion

[0077] 1.5 parts of sodium dodecyl sulfate and 2.5 parts of potassium oleate were added to 91 parts of deionized water and stirred to dissolve, and then 5 parts of carbon black (purchased from Cabot Corporation of the United States, model Monarch800 (M800)) were added, and placed in a high shear dispersing homogenizer at a speed of 8-10 kr / min for 10 minutes to obtain a nano-scale carbon black emulsion (C1), wherein the particle size of the carbon black is 80-150 nm, and its transmission electron microscope photo is as shown in FIG. Figure 1 As shown, the irregularly shaped particles are carbon black particles.

[0078] (3) Preparation of rubber phase coated with colorant

[0079] 9.5 parts of the polysiloxane latex (G1) obtained in step (1) (3 parts in terms of the solid content in the polysiloxane latex), 46 parts of the nano-scale carbon black emulsion (C1) obtained in step (2) (2.3 parts in terms of the carbon black content in the nano-scale carbon black emulsion), 52 parts of butyl acrylate, 0.5 parts of dicyclopentadiene acrylate, 0.4 parts of sodium dodecyl sulfate and 100 parts of deionized water were added to a four-necked flask with a nitrogen tube, a thermometer, a reflux device and a stirring device. After stirring for 1 hour, the mixture was heated to 70°C, 0.15 parts of potassium persulfate were added, and the reaction was maintained at 70°C for 3 hours to obtain a rubber core emulsion, i.e., a rubber phase (A1) coated with carbon black.

[0080] (4) Preparation of an emulsion of a silicon-modified acrylate-styrene-acrylonitrile graft copolymer coated with a colorant

[0081] In a four-necked flask with a nitrogen tube, a thermometer, a reflux device and a stirring device, 208.55 parts of the rubber phase (A1) coated with carbon black obtained in step (3), 0.3 parts of glucose, 0.2 parts of sodium pyrophosphate, 0.03 parts of ferrous sulfate heptahydrate, and 10 parts of deionized water were added, and the temperature was raised to 65-70°C. 32.5 parts of styrene, 12.5 parts of acrylonitrile, 0.07 parts of n-dodecyl mercaptan, 0.14 parts of cumene hydroperoxide, 0.2 parts of sodium dodecyl sulfate, 0.4 parts of diphenyloxy sulfonate and 45 parts of deionized water were mixed and homogenized at high speed, and then added dropwise to the above four-necked flask, and the mixture was added dropwise for 3 hours, and the mixture was kept at 70°C for 1.5-2 hours to obtain a silicon-modified ASA emulsion (A2) coated with carbon black, with a particle size of 140 nm. The transmission electron microscope photograph thereof is shown in FIG. Figure 2 As shown, Figure 1 In comparison, Figure 2 The coated particles are all regular spherical particles, and there is no irregularly shaped carbon black.

[0082] (5) Preparation of silicon-modified ASA high-rubber powder coated with carbon black

[0083] Add 1 wt % calcium chloride solution to the ASA emulsion (A2) obtained in step (4) (add 0.75 kg of 1 wt % calcium chloride solution to 1 kg of ASA emulsion (A2)), heat to 70° C. to break the emulsion, wash with water and centrifuge, then put into a vacuum drying oven and dry at 80° C. for 24 hours to obtain a silicon-modified ASA high-rubber powder coated with carbon black, wherein the number average molecular weight (Mn) is 57,000, the weight average molecular weight (Mw) is 128,000, and the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) is 2.25.

[0084] Example 2

[0085] The steps are similar to those in Example 1, except that 46 parts of carbon black emulsion (C1) (2.3 parts based on the carbon black component in the carbon black emulsion) in step (3) are replaced with 11.4 parts of carbon black emulsion (C1) (0.57 parts based on the carbon black component in the carbon black emulsion) and 34.6 parts of deionized water. Silicon-modified ASA high-rubber powder coated with carbon black is obtained.

[0086] Comparative Example 1

[0087] The steps are similar to those in Example 1, except that 46 parts of carbon black emulsion (C1) (2.3 parts based on the carbon black component in the carbon black emulsion) in step (3) are replaced by 46 parts of deionized water to obtain silicon-modified ASA high-rubber powder.

[0088] Example 3

[0089] (1) Preparation of polysiloxane latex

[0090] Same as Example 1.

[0091] (2) Preparation of colorant emulsion

[0092] 2.0 parts of sodium dodecyl sulfate and 2.0 parts of potassium oleate were added to 91 parts of deionized water and stirred to dissolve. Then 5 parts of black organic dye (purchased from Sumitomo Chemical Co., Ltd., Japan, H3B) were added and placed in a high shear dispersing homogenizer and homogenized and dispersed at a speed of 8-10 kr / min for 10 minutes to obtain a black organic dye emulsion (R1).

[0093] (3) Preparation of rubber phase coated with colorant

[0094] The steps are similar to those in Example 1, except that 46 parts of the carbon black emulsion (C1) (2.3 parts based on the carbon black component in the carbon black emulsion) in this step are replaced by 17.15 parts of the black organic dye emulsion (R1) obtained in step (2) (0.86 parts based on the black organic dye component) and 28.85 parts of deionized water.

[0095] (4) Preparation of an emulsion of a silicon-modified acrylate-styrene-acrylonitrile graft copolymer coated with a colorant and (5) Preparation of a silicon-modified ASA high-rubber powder coated with carbon black

[0096] Same as Example 1.

[0097] Preparation and evaluation of compositions

[0098] According to the ratios described in the following application examples, the raw materials were premixed in a high-speed mixer (Dongguan Kede Machinery Co., Ltd., HRS-10); the obtained premix was melt-extruded at an extrusion temperature of 230° C. through a twin-screw extruder (Nanjing Keya Chemical Complete Equipment Co., Ltd., model: HK 26), cooled and granulated to obtain an AS / ASA resin composition or a PMMA / ASA alloy material. Then, it was injection molded at 235° C.

[0099] According to the requirements, the molded composition was made into test pieces for impact test, combustion test, coloring test and gloss test. The pellets and test pieces were used to evaluate the properties such as impact strength, flame retardancy, coloring and gloss. The results are shown in Tables 1 and 2.

[0100] Application Example 1

[0101] Application Example 1 provides an AS / ASA resin composition, the raw material composition of which is as follows:

[0102]

[0103]

[0104] The weighed raw materials are premixed in a high-speed mixer; the obtained premix is ​​melt-extruded at an extrusion temperature of 230° C. through a twin-screw extruder, cooled and granulated to obtain an AS / ASA resin composition; and then injection molded at 235° C.

[0105] Application Comparative Example 1

[0106] Application Comparative Example 1 provides an AS / ASA resin composition, the raw material composition of which is as follows:

[0107]

[0108] The preparation process is the same as that of Application Example 1.

[0109] Table 1

[0110] Detection items Application Example 1 Application Comparative Example 1 <![CDATA[Notch impact kJ / m 2 > 16.0 16.3 Melt index g / 10min 12.0 12.8 L 26.5 26.7 a -0.01 -0.04 b -1.98 -2.12 Glossiness 98 98

[0111] In the results of Table 1, the smaller the L value, the better the blackness. The larger the absolute value of the b value, the more bluish the visual blackness is, and the smaller the absolute value of the b value, the more yellowish the visual blackness is, and the darker the visual blackness is. From the physical property test, the application example 1 of the coated colorant carbon black (the carbon black in the ASA high rubber powder of Example 1 in the application example 1 is converted into a formula of the composition of about 0.8 parts) has a lower L value and a smaller absolute value of the b value compared with the application comparison example 1. Therefore, the visual blackness of the product of the application example 1 is darker. The same number of parts of the colorant carbon black added in the application example 1 has a higher blackness than that in the application comparison example 1 due to better dispersibility, and the original processing performance can be maintained due to the little change in the notched impact and melt index.

[0112] Application Example 2

[0113] Application Example 2 provides a PMMA / ASA alloy material, the raw material composition of which is as follows:

[0114]

[0115] The preparation process is the same as that of Application Example 1, and a PMMA / ASA alloy material after injection molding is obtained.

[0116] Application Comparative Example 2

[0117] Application Comparative Example 2 provides a PMMA / ASA alloy material, the raw material composition of which is as follows:

[0118]

[0119] The preparation process is the same as that of Application Example 1, and a PMMA / ASA alloy material after injection molding is obtained.

[0120] Application Example 3

[0121] Application Example 3 provides a PMMA / ASA alloy material, the raw material composition of which is as follows:

[0122]

[0123]

[0124] The preparation process is the same as that of Application Example 1, and a PMMA / ASA alloy material after injection molding is obtained.

[0125] Application Comparative Example 3

[0126] Application Comparative Example 3 provides a PMMA / ASA alloy material, the raw material composition of which is as follows:

[0127]

[0128] The preparation process is the same as that of Application Example 1, and a PMMA / ASA alloy material after injection molding is obtained.

[0129] Table 2

[0130]

[0131] In the results of Table 2, the smaller the L value, the better the blackness. The larger the absolute value of the b value, the more bluish the visual blackness is, and the smaller the absolute value of the b value, the more yellowish the visual blackness is, and the darker the visual blackness is. From the physical property test, the application example 2 of the coated colorant carbon black (the carbon black in the ASA high rubber powder of Example 2 in the application example 2 is converted into a formula of the composition of about 0.2 parts) has a lower L value and a smaller absolute value of the b value (reduced by about 20%) compared with the application comparison example 2. Therefore, the product of the application example 2 can achieve better coloring blackness and visual blackness with the same amount of carbon black added.

[0132] The same black organic dye coated application example 3 (the black organic dye in the ASA high-rubber powder of example 3 in application example 3 is converted into a composition formula of about 0.3 parts) has a lower L value and a smaller absolute value of b value than the application comparative example 3. Therefore, the product of application example 3 can achieve better coloring blackness and visual blackness with the same amount of black organic dye added.

[0133] The above embodiments are preferred implementation modes of the present invention, but the present invention is not limited to these embodiments. As long as they do not deviate from the spirit and principle of the present invention, the changes, modifications, substitutions, combinations and simplifications made to the above embodiments are deemed to be equivalent replacement methods and are included in the protection scope of the present invention.

[0134] Industrial Applicability

[0135] The colorant-coated silicon-modified acrylate-styrene-acrylonitrile graft copolymer of the present invention can be mixed with a resin to prepare a composition with better coloring blackness. The composition of the present invention can be widely used in high-gloss black ASA products such as automobile grille bodies, rearview mirror housings, pillar decorative panels, tailgate decorative panels, etc.

Claims

1. A method for preparing a colorant-coated silicon-modified acrylate-styrene-acrylonitrile graft copolymer, characterized in that: The following steps are involved: Dispersing the colorant in the emulsifier solution to form a nano-scale colorant emulsion; In the presence of the nano-scale colorant emulsion, polymerizing the polysiloxane latex and the acrylic ester to obtain a rubber phase coated with the colorant; and The obtained rubber phase is grafted with styrene and acrylonitrile to obtain an emulsion of a silicon-modified acrylate-styrene-acrylonitrile graft copolymer coated with a colorant.

2. The preparation method according to claim 1, characterized in that: The colorant is selected from carbon black or black organic dyes, When the total amount of the solid content of the polysiloxane latex, the acrylic ester, the styrene, and the acrylonitrile added is taken as 100 parts by weight, the amount of the colorant added is 0.3 to 3 parts by weight.

3. The preparation method according to claim 2, characterized in that: When the colorant is carbon black, the amount of carbon black added is 0.5-2.3 parts by weight; When the colorant is a black organic dye, the added amount of the black organic dye is 0.5-1.2 parts by weight.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The emulsifier used to disperse the colorant is selected from one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, dodecylbenzene sulfonic acid and its sodium salt, potassium oleate, sodium stearate, disproportionated potassium rosin soap, dioctyl sodium sulfosuccinate, sodium salt of dihexyl sulfosuccinate and polyethylene glycol trimethyl nonyl ether, preferably a combination of sodium dodecyl sulfate and potassium oleate.

5. The preparation method according to any one of claims 1 to 3, characterized in that: When the total amount of the solid content of the polysiloxane latex, the acrylic ester, the styrene, and the acrylonitrile is calculated as 100wt%, the added amount of the polysiloxane latex in terms of solid content is 2-10wt%, preferably 3-6wt%; the added amount of the acrylic ester is 48-58wt%, preferably 50-55wt%; the added amount of the styrene is 25-40wt%; and the added amount of the acrylonitrile is 10-25wt%.

6. The preparation method according to claim 5, characterized in that: The styrene accounts for 67-80 wt %, preferably 70-78 wt %, of the total amount of the styrene and the acrylonitrile.

7. The preparation method according to any one of claims 1 to 3, characterized in that: The polysiloxane latex is a latex of a linear polysiloxane having a vinyl group, and the content of the vinyl group in the polysiloxane latex relative to the solid content in the polysiloxane latex is 0.01 to 3 wt %.

8. The preparation method according to claim 7, characterized in that: The polysiloxane latex is obtained by polymerizing a dimethylsiloxane monomer, a vinylsiloxane monomer, and a capping agent as required, and the number average molecular weight Mn of the polysiloxane latex is 200,000 to 600,000.

9. The preparation method according to claim 8, characterized in that: The dimethylsiloxane monomer is selected from one or more of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane; The vinyl siloxane monomer is selected from one or more of γ-(meth)acryloxypropyldimethoxymethylsilane, γ-(meth)acryloxypropyldiethoxymethylsilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, and tetramethyltetravinylcyclotetrasiloxane; The capping agent is selected from one or more of hexamethyldisiloxane, tetramethyldivinyldisiloxane, methoxytrimethylsilane, ethoxytrimethylsiloxane, dimethylvinylmethoxysilane, and dimethylvinylethoxysilane.

10. The preparation method according to any one of claims 1 to 3, characterized in that: The particle size of the latex of the colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer is 80-200 nm, preferably 100-150 nm.

11. The preparation method according to any one of claims 1 to 3, characterized in that: The rubber phase coated with the colorant is obtained by polymerizing the polysiloxane latex and the acrylic ester using a crosslinking agent, The crosslinking agent is selected from one or more of divinylbenzene, dicyclopentadiene acrylate, allyl methacrylate, diallyl phthalate, mono[2(1-oxy-2-propenyl)oxyethyl] maleate, and trimethylolpropane triacrylate, preferably dicyclopentadiene acrylate.

12. The preparation method according to any one of claims 1 to 3, characterized in that: The rubber phase coated with the colorant is grafted with the styrene and the acrylonitrile by using an initiator to obtain an emulsion of the silicon-modified acrylate-styrene-acrylonitrile graft copolymer coated with the colorant, The initiator is selected from one or more of perazobisisobutyronitrile, potassium persulfate, ammonium persulfate, glucose, vitamin C, cumene hydroperoxide, and tert-butyl hydroperoxide, preferably glucose and / or cumene hydroperoxide.

13. The preparation method according to any one of claims 1 to 3, characterized in that: The method also includes the step of preparing high-rubber powder from the emulsion of the colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer.

14. A colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer obtained by the preparation method according to any one of claims 1 to 13.

15. The colorant-encapsulated silicon-modified acrylate-styrene-acrylonitrile graft copolymer according to claim 14, characterized in that: The number average molecular weight (Mn) thereof is 40,000-70,000, the weight average molecular weight (Mw) is 110,000-140,000, and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is 2.1-3.

4.

16. A composition, characterized in that: A silicon-modified acrylate-styrene-acrylonitrile graft copolymer and a resin containing the coated colorant according to claim 14 or 15, wherein the resin is selected from one or more of styrene-acrylonitrile copolymer, polymethyl methacrylate, polycarbonate, polybutylene terephthalate, polystyrene, (meth)acrylate-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-ethylene-propylene rubber-styrene copolymer, and polyethylene terephthalate, preferably one or more of styrene-acrylonitrile copolymer, polymethyl methacrylate, and polycarbonate.

17. The composition according to claim 16, characterized in that: The content of the silicon-modified acrylate-styrene-acrylonitrile graft copolymer encapsulating the colorant is 28-40wt%, preferably 30-36wt%.

18. The composition according to claim 16 or 17, characterized in that: The composition is a resin composition or an alloy material. The resin composition preferably includes a styrene-acrylonitrile copolymer and the silicon-modified acrylate-styrene-acrylonitrile graft copolymer of the coated colorant. The alloy material preferably includes polymethyl methacrylate and the silicon-modified acrylate-styrene-acrylonitrile graft copolymer of the coated colorant.

Citation Information

Patent Citations

  • Vinyl grafted copolymer, resin composite containing same and preparation method of vinyl grafted copolymer

    CN106519144A

  • High-weather-resistance high-gloss black ASA resin composition and preparation method thereof

    CN109401103A

  • PMMA / ASA alloy material with high heat resistance and high black brightness and preparation method and application of PMMA / ASA alloy material

    CN111690222A

  • High-gloss black scratch-resistant PMMA / ASA composite material and preparation method thereof

    CN112552614A

  • Spraying-free metal-texture high-gloss high-weather-resistance PMMA / ASA alloy material and preparation method thereof

    CN113416372A